1998
DOI: 10.1046/j.1365-2230.1998.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic fibroma of the skin, a form of sclerotic fibroma: an immunohistochemical study

Abstract: We report a new case of pleomorphic fibroma of the skin arising on the face. The lesion was polypoid and fibrous, located on the dermis, and formed by coarse collagen bundles with sparse cells. It was also characterized by the presence of cellular atypia and pleomorphism without mitosis. Immunohistochemistry showed staining for vimentin and actin and negativity for S-100, CD34, CD68, alpha-1-antichymotrypsin and alpha-1-antitrypsin antigens, supporting a myofibroblastic origin. A few isolated cells also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 6 publications
3
27
0
Order By: Relevance
“…These findings raised the question of a possible preceding chronic folliculitis or a keratin cyst that ruptured. Finally, the prominent cellular component observed in our patient, which has been previously reported in a few case reports, was alarming especially that it occurred in a pediatric patient 3–8 . This histological feature raised a differential diagnosis that mainly includes other spindle cell tumors such as fibrous tumors (dermatofibrosarcoma protuberans, pleomorphic fibroma and keloid), as well as tumors of neural, melanocytic and muscle origin.…”
supporting
confidence: 52%
“…These findings raised the question of a possible preceding chronic folliculitis or a keratin cyst that ruptured. Finally, the prominent cellular component observed in our patient, which has been previously reported in a few case reports, was alarming especially that it occurred in a pediatric patient 3–8 . This histological feature raised a differential diagnosis that mainly includes other spindle cell tumors such as fibrous tumors (dermatofibrosarcoma protuberans, pleomorphic fibroma and keloid), as well as tumors of neural, melanocytic and muscle origin.…”
supporting
confidence: 52%
“…[13] Degeneration, ischemia, or the paracrine influence of mast cells may create the cytological atypia in PF. [145] Two variants have been described: Myxoid and sclerotic. [67] In fact, some investigators have postulated that the PF of the skin is actually a variant of the sclerotic fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…[67] In fact, some investigators have postulated that the PF of the skin is actually a variant of the sclerotic fibroma. [48] Other researchers have called these as pleomorphic sclerotic fibromas. [9]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the atypical cytologic features, the proliferative index was low with rarely identified cells in mitosis and clinical follow up was benign. Additional reports demonstrate that pleomorphic fibroma may exhibit marked variability in stromal alteration, ranging from sclerotic to fibrotic to myxoid, and may pose a diagnostic challenge in some cases . In cases with exuberant sclerosis, some authors have identified immunohistochemical overlap with sclerotic fibroma (sclerotic pleomorphic fibroma) …”
Section: Introductionmentioning
confidence: 99%